2020
DOI: 10.1038/s41586-019-1907-7
|View full text |Cite|
|
Sign up to set email alerts
|

The evolutionary history of 2,658 cancers

Abstract: Cancer develops through a process of somatic evolution 1,2. Sequencing data from a single biopsy represent a snapshot of this process that can reveal the timing of specific genomic aberrations and the changing influence of mutational processes 3. Here, by whole-genome sequencing analysis of 2,658 cancers as part of the Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium of the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA) 4 , we reconstruct the life history and evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
541
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 769 publications
(596 citation statements)
references
References 48 publications
28
541
1
Order By: Relevance
“…Efficient amplification of the targets from cfDNA templates is expected with an amplicon size of ~ 150 bp, corresponding to the median size of the cfDNA [5], a finding supported by an earlier study that reported an increase (5-20-fold) in the percentage of mutant molecules of the adenomatous polyposis coli (APC) gene when the template size was decreased from 1296 to 100 bp [6]. Furthermore, a recent study identified that apart from variants (KRAS and TP53), copy number alterations (CNAs-17p, 9p, ARID1A, 18q, 9p213, SMAD4) are preferentially altered early in the tumorigenesis process [7]. This suggests that for effective identification of early tumorigenesis, it is not only the variants that have to genotyped but CNAs also have to be assessed.…”
supporting
confidence: 63%
“…Efficient amplification of the targets from cfDNA templates is expected with an amplicon size of ~ 150 bp, corresponding to the median size of the cfDNA [5], a finding supported by an earlier study that reported an increase (5-20-fold) in the percentage of mutant molecules of the adenomatous polyposis coli (APC) gene when the template size was decreased from 1296 to 100 bp [6]. Furthermore, a recent study identified that apart from variants (KRAS and TP53), copy number alterations (CNAs-17p, 9p, ARID1A, 18q, 9p213, SMAD4) are preferentially altered early in the tumorigenesis process [7]. This suggests that for effective identification of early tumorigenesis, it is not only the variants that have to genotyped but CNAs also have to be assessed.…”
supporting
confidence: 63%
“…46 Copy-number dataset. We analyzed copy-number profiles obtained by the PCAWG Evolution and Heterogeneity Working Group, using a consensus approach that combines six different state-of-the-art copy-number calling methods 49 . GC content corrected logR values were extracted using the Battenberg algorithm 50 , smoothed using a running median and transformed into copy-number space according to n = [(2(1 − ρ) + ψρ)2 logR − 2(1 − ρ)]/ρ where ρ and ψ are consensus tumor purity and ploidy, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the uniformly processed and highly curated sets of all classes of somatic mutations from the 2,780 cancer genomes of the PCAWG project 2 , combined with most other suitable cancer genomes (accession code syn11801889, available at https://www.synapse.org/#!Synapse:syn11801889), present a notable opportunity to establish the repertoire of mutational signatures and determine their activities across different types of cancer. The timing of these signatures during the evolution of individual cancers and the repertoire of signatures of structural variation have been explored in other PCAWG analyses 30,34 .…”
mentioning
confidence: 99%